Flexural impact response and damage detection of composite sandwich beam with various PVC foam cores. Issue 9 (4th April 2022) - Caliskan, Umut; Apalak, M. Kemal
Abstract: This article investigates the flexural impact and damage behavior of composite sandwich beam in terms of foam core effect using the micro-computerized tomography, Micro-CT. Foam core is dominant on the damage behavior of sandwich structures. As the python scripting language was used parametric modeling, the intra-laminar damage was created with the three-dimensional explicit finite element subroutine and implemented to ABAQUS as VUMAT via FORTRAN. The results of the FEM were found to agree well with experimental observations. Notably, the change in foam core density has a very high effect on contact force levels, impact trend and damage progress.